2017
DOI: 10.1080/10508619.2018.1415085
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Delight and Endless Night: A Qualitative Exploration of Ordinary and Extraordinary Religious and Spiritual Experiences in Bipolar Disorder

Abstract: The authenticity of religious and spiritual experiences during mania is an important subject for bipolar patients. The exploration of such experience in bipolar disorder is the central point of this qualitative study. A psychiatrist and a hospital chaplain conducted 35 semi-structured interviews with recovered participants, recruited from mental health care institutions in the Netherlands, the patients' association and via the internet, about their religious and spiritual experiences during illness episodes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…Jerome Kroll and William Sheehan (1989), reported an incidence of 55% of 'personal religious experiences' during a manic episode versus 35% of the general population having 'personal religious experiences' in a subsample (n = 11) with BD of a larger inpatient group. Ouwehand et al (2018Ouwehand et al ( , 2019a found that the occurrence of specific self-reported religious or spiritual experiences of persons with BD did not differ much from frequencies of comparable experiences in the general population. However, these experiences occurred significantly more often in persons with bipolar I disorder (BD I) than with bipolar II disorder (BD II) and were reported as occurring more often during mania than not.…”
Section: Religious Experiences and Bdmentioning
confidence: 95%
“…Jerome Kroll and William Sheehan (1989), reported an incidence of 55% of 'personal religious experiences' during a manic episode versus 35% of the general population having 'personal religious experiences' in a subsample (n = 11) with BD of a larger inpatient group. Ouwehand et al (2018Ouwehand et al ( , 2019a found that the occurrence of specific self-reported religious or spiritual experiences of persons with BD did not differ much from frequencies of comparable experiences in the general population. However, these experiences occurred significantly more often in persons with bipolar I disorder (BD I) than with bipolar II disorder (BD II) and were reported as occurring more often during mania than not.…”
Section: Religious Experiences and Bdmentioning
confidence: 95%
“…Very few studies concerning the religious experiences of people with BD are available (Gallemore Jr et al 1969;Kroll and Sheehan 1989;Ouwehand et al 2018). Studies of the interpretation of religious experiences of persons with a bipolar diagnosis are not known to the authors; this is the focus of the current study.…”
Section: Religious Experience and Bipolar Disordermentioning
confidence: 97%
“…Hitherto, there has been little research done into the kinds of religious experience that can occur in BD and the influence such experiences have on persons with this diagnosis. A qualitative study (Ouwehand et al 2018) indicated different types of self-reported religious and spiritual experiences in BD, predominantly occurring during mania. Most mentioned were experiences of the presence of a transcendental reality, either divine or more this-worldly, of unity, of vocation/mission, or of meaningful synchronicity.…”
Section: Religious Experience and Bipolar Disordermentioning
confidence: 99%
See 2 more Smart Citations